Osmyloberotha, an unusual new genus of beaded lacewings (Neuroptera: Berothidae) from Burmese amber - Khramov, Alexander V. (Zootaxa, 2021)
A new beaded lacewing, Osmyloberotha simpla gen. et sp. nov. (Neuroptera: Berothidae), is described from Cenomanian Burmese amber (Myanmar, Kachin State). It has a rather peculiar osmylid-like venation with simple costal veinlets and CuA, CuP, A1 and A2 all pectinate in forewing, a venational pattern previously unknown in Berothidae.